Use of population data for assessing trends in work-related asthma mortality. Issue 2 (April 2019) - Mazurek, Jacek M.; Henneberger, Paul K.
Abstract : Purpose of review: Work-related asthma has been associated with poorer asthma control and frequent unscheduled healthcare visits, and can be fatal. Case reports of work-related asthma deaths are rare, but can initiate efforts to prevent additional cases. We reviewed relevant literature and data sources to evaluate whether analyzing mortality data at the population level can help identify potential sources of exposures that contribute to work-related asthma. Recent findings: A limited number of population-based studies have addressed work-related asthma mortality. Data on asthma mortality are derived from death certificates using the International Classification of Diseases (ICD) as a standard for coding cause. However, no discrete code for work-related asthma is available. Analysis of asthma mortality relative to industries and occupations appears to identify high-risk jobs that were not identified by analyzing asthma morbidity data. Summary: Beyond recognized work-related asthma deaths, it is possible that occupational exposures have contributed to other asthma deaths that have gone unnoticed and could potentially be identified by the analysis of mortality data at the population level. Such analyses in the United States appear to assist in recognizing high-risk occupations and industries. Additional analyses would be possible if a work-related asthma ICD code were available.